Single-Cell Analysis of Circulating Tumor Cells: How Far Have We Come in the -Omics Era? - Rossi, Elisabetta; Zamarchi, Rita (Frontiers in Genetics, 2019)
Detaching themselves from the primary tumor or metastatic sites, tumor cells reach peripheral blood, often causing metastasis. Named Circulating Tumor Cells, CTCs display spatial and temporal heterogeneity as the primary tumor. Since CTCs are a crucial step in tumor progression, they represent a privileged field to disclose metastasis’ mechanisms, whilst the –omic analyses at single-cell level allow to dissect the complex relationships between the tumor subpopulations and the surrounding normal tissue. However, in addition to reporting the proof of concept that we can query CTCs for disclosing tumor evolution throughout the continuum of treatment, hoping to early detect the resistance to therapy, scientific literature has also been underlining the disadvantages of CTCs, which hamper a routine use of this approach in clinical practice. To date, an increasing number of CTC’ technologies, as well as –omics methods have been employed, mostly lacking a strong comparative analysis. The rarity of CTCs also represents a major challenge, because there is no consensus regarding the minimal criteria necessary and sufficient to define an event as CTC; moreover, we cannot often compare data from of one study with another. Finally, the availability of an individual tumor profile undermines the traditional histology-based treatment. Applying molecular data for patients’ benefit implies a collective effort of biologists, bioengineers and clinicians, to create tools to interpret molecular data and manage precision medicine in every single patient. Herein, we focus on the most recent findings in CTC’ omics to update how far we have come.